Researching female genital mutilation/cutting Proceedings of the 2nd International Academic Seminar of MAP-FGM Project - Leye, Els; Coene, Gily (ASP editions - Academic and Scientific Publishers, 2017)
This volume consist of papers which provide an overview of the presentations at the Second International Academic Seminar: Female Genital Mutilation/Cutting at the intersection of qualitative, quantitative and mixed method research. Experiences from Africa and Europe. This seminar took place June 2017, in Brussels. The contributions in this book focus on research's crucial role in abandoning female genital mutilation/ cutting (FGM/C), gaps in the research, the need to integrate an intersectionality perspective in the research and evaluations of current strategies for abandoning the practice.